HAEMOPHILUS INFLUENZAE INFECTION IN CHILDREN DURING SPORADIC MORBIDITY: CLINICAL CASES WITH DIFFERENT (FAVORABLE OR FATAL) OUTCOMES - Gennadii A. Kharchenko; Olga G. Kimirilova ("Paediatrician" Publishers LLC, 2017)
Haemophilus influenzae infection in children is detected as sporadic cases and is characterized by polymorphism of clinical symptoms (rhinopharyngitis, purulent meningitis, acute epiglottitis, panniculitis, etc.), which complicates an early diagnosis and treatment of this pathology. In young children, Haemophilus influenzae infection (type b) often occurs in generalized forms and may result in death. The article presents  literature data and the results of own clinical observations  of Haemophilus influenzae cases that occurred with an aspect of purulent meningitis and panniculitis in young children. The tactics of a complex therapy and ways to prevent Haemophilus in fluenzae infection are discussed.